Rafael Antonio Díaz Díaz. "Esclavitud, región y ciudad: El sistema esclavista urbanoregional en Santafé de Bogotá, 1700-1750". Bogotá: Centro Editorial Javeriano, 2001. - Valencia Villa, Carlos Eduardo (Fronteras de la historia, 2002)
.